Comparative responsiveness and minimally important difference of Fatigue Symptom Inventory (FSI) scales and the FSI-3 in trials with cancer survivors - Catherine E. Mosher; Ekin Secinti; Shelley A. Johns; Kurt Kroenke; Laura Q. Rogers (SpringerOpen, 2022)
Plain English Summary Fatigue is a highly prevalent and disabling symptom in cancer survivors. Although many measures have been developed to assess survivors' fatigue, their ability to accurately capture change following intervention has rarely been assessed in post-treatment survivors. A minimally important difference in fatigue, or clinically meaningful change, also has rarely been documented for fatigue scales in studies of post-treatment survivors. Ultra-brief fatigue measures are preferable in clinical practice, but have limited evidence supporting their use with cancer survivors. This study aimed to address these gaps in the literature through analyses of Fatigue Symptom Inventory (FSI) data from three randomized behavioral intervention trials with post-treatment cancer survivors (N = 328). Four FSI measures (i.e., FSI total score, FSI severity and interference subscales, and the FSI-3) showed comparable ability to detect change in fatigue and responsiveness to intervention with cancer survivors. Estimated minimally important differences ranged from 0.29 to 2.20 across FSI measures and warrant further study to inform assessment of meaningful score change in research and clinical practice. Results support continued use of the FSI with cancer survivors and provide initial evidence for use of the ultra-brief FSI-3 measure.